LEGAL POLITICS CONCERNING THE FULFILLMENT OF LGBT CONSTITUTIONAL RIGHTS IN THE INDONESIAN LEGAL APPROACH - Ahmad Gelora Mahardika (Pusat Studi Gender dan Anak, 2023)
Article 28 E paragraph (2) of the 1945 Constitution of the Republic of Indonesia states that everyone has the right to believe in beliefs and express thoughts and attitudes according to his conscience. These provisions are the basis that no one can judge his choices and attitudes. On the other hand, LGBT, as a minority group in Indonesia, often receive unpleasant treatment for their sexual orientation. Referring to WHO data, LGBT cannot categorize as a genetic and natural disease. As a legal state that upholds human rights, the state should protect LGBT people. Such protection can carry out through appropriate legal politics by forming several regulations that allow LGBT people to get the same constitutional rights as others. This policy is essential to manifest the state's presence towards all community groups without exception. Based on these things, this article aims to answer the question of the proper legal policy to provide human rights protection for LGBT groups in Indonesia. The research method used in this article is normative juridical. This article hypothesizes that the correct political law will allow LGBT groups to obtain the same rights as other people.